Riqueza e composição de espécies de formigas no processo de recuperação de uma voçoroca - Biagiotti, Gabriel [UNESP]; Pereira, José Aldo Alves; Ribas, Carla Rodrigues; Korasaki, Vanesca; Zanetti, Ronald; Queiroz, Antônio César Medeiros De (Universidade Federal de Lavras (UFLA), 2013)
This study aimed to determine how the richness and composition of ant species behaves with changes in the recovery process of a gully erosion. The study area has 0.9 hectares subdivided into three sections called sector: A, B and C. For the definition of the sectors, erosive and natural restoring were taken as the base level of activity. Four transects were laid systematically throughout the area and surrounding compound with forest and grassland. Each transect had three pitfall trap ten meters apart from each other, with catches of ants were held in rainy and dry seasons. Analysis of variance was applied to compare the number of ant species per plot captured and Scott-Knott test 5% for comparison of means. To verify the similarity of species between environments it was performed an analysis of similarity (ANOSIM) and ordering of environments a Nonmetric Multidimensional Scaling (NMDS). We captured 74 species of ants inside and around the gully erosion. The more degraded environment and initial stage of regeneration, showed greater richness of ant species. The composition of ant species was different between the recovery environments and around. The parameters of ant communities analyzed, richness and composition species were influenced by the regeneration of the area, indicating that ants can be used as bioindicators of gullies recovery.

Neste trabalho, objetivou-se verificar como a riqueza e a composição de espécies de formigas se comporta com as mudanças ocorridas no processo de recuperação de uma voçoroca. A área em estudo possui 0,9 hectares subdivididos em três setores denominados braços: A; B e C. Para a definição dos setores tomou-se como base o nível de atividade erosiva e a regeneração natural. Foram lançadas quatro transeções de forma sistemática na área da voçoroca e no entorno composto com mata e pastagem. Cada transeção possuía três armadilhas do tipo pitfall distante entre si 10 metros, sendo que as capturas de formigas foram realizadas em duas épocas, chuvosa e seca. Foi realizada uma análise de variância para comparar o número de espécies de formigas capturadas por parcela nos ambientes e aplicado teste Scott-Knott a 5% para comparação das médias. Para verificar a similaridade de espécies entre os ambientes foi realizada uma análise de similaridade (ANOSIM) e para a ordenação dos ambientes uma Nonmetric Multidimensional Scaling (NMDS). Foram capturadas 74 espécies de formigas no interior da voçoroca e no entorno. O ambiente mais degradado e em estágio inicial de regeneração, apresentou maior riqueza de espécies de formigas. A composição de espécies de formigas foi diferente entre os ambientes em recuperação e o entorno. Os parâmetros das comunidades de formigas analisados, riqueza e composição de espécies, foram influenciados pela regeneração da área, indicando que as formigas podem ser usadas como bioindicadoras de recuperação de voçorocas.
Richness and species composition of ants in the recovery process of a gully erosion
Keywords: Áreas degradadas; monitoramento ambiental; formicidae; Degraded areas; environmental monitoring; formicidae